Criminal Liability of Child Perpetrators of Sexual Offenses: A Study of Decision Number 4/Pid.Sus-Anak/2025/PN Pgp from the Perspective of the Child Criminal Justice System - Novianda, Riescha; Saliman, Abdul Rasyid; Agustina, Enny (GoAcademica Research & Publishing, 2025)
This study examines the criminal responsibility of a child perpetrator of sexual intercourse offenses under Indonesia’s juvenile justice system, focusing on the analysis of the District Court of Pangkalpinang Decision Number 4/Pid.Sus-Anak/2025/PN Pgp. The child was sentenced to three months in a Special Child Development Institution and required to participate in a three-month vocational training program. The sentence was conditional, emphasizing rehabilitative and educational approaches. This research aims to assess the alignment of the judicial verdict with the principles of Law Number 11 of 2012 on the Juvenile Criminal Justice System, particularly the application of restorative justice and non-penal approaches for juvenile offenders. Employing normative juridical methods and a case study approach, this paper reveals that the conditional sentence and vocational training illustrate a concrete application of juvenile criminal punishment prioritizing the child’s best interests and legal protection. Furthermore, the involvement of legal counsel, social advisors, and the child’s parents signifies the practical implementation of restorative justice principles within juvenile court proceedings.